Differential Cytotoxic Function of Resident and Non-resident CD8+ T Cells in the Human Female Reproductive Tract Before and After Menopause - Rodriguez-Garcia, Marta; Shen, Zheng; Fortier, Jared M.; Wira, Charles R. (Frontiers in Immunology, 2020)
The functional characterization and regulation of tissue resident and non-resident CD8+ T cells in the human female reproductive tract (FRT) as women age remains a gap in our knowledge. Here we characterized the cytotoxic activity and granular contents of CD8+ T cells from the FRT in pre- and postmenopausal women. We found that under steady-state conditions, CD8+ T cells from endometrium (EM), endocervix and ectocervix displayed direct cytotoxic activity, and that cytotoxicity increased in the EM after menopause. Cytotoxic activity was sensitive to suppression by TGFβ exclusively in the EM, and sensitivity to TGFβ was reduced after menopause. Under steady-state conditions, cytotoxic activity (measured as direct killing activity), cytotoxic potential (measured as content of cytotoxic molecules) and proliferation are enhanced in non-resident CD8+ (CD103-) T cells compared to tissue resident (CD103+) T cells. Upon activation, CD103+ T cells displayed greater degranulation compared to CD103- T cells, however the granular content of perforin, granzyme A (GZA) or granzyme B (GZB) was significantly lower. After menopause, degranulation significantly increased, and granular release switched from predominantly GZB in premenopausal to GZA in postmenopausal women. Postmenopausal changes affected both CD103+ and CD103- subpopulations. Finally, CD103+ T cells displayed reduced proliferation compared to CD103- T cells, but after proliferation, cytotoxic molecules were similar in each population. Our results highlight the complexity of regulation of cytotoxic function in the FRT before and after menopause, and are relevant to the development of protective strategies against genital infections and gynecological cancers as women age.